Study of Drainage Capacity in Ujung Kalak Village, West Aceh District - Meylis Safriani; Inseun Yuri Salena; M Arrie Rafsanjani; Isdaryanto Iskandar (International Journal of Engineering, Science and Information Technology, 2022)
Flood inundation occurs on main roads in Meulaboh City, especially when it rains. Johan Pahlawan District is one of the sub-districts in West Aceh Regency. This sub-district includes a densely populated area of 4243 people, which is in the urban area of Meulaboh City One is the road in Ujung Kalak Village, where floods often occur even though the village already has drainage. A study of the drainage profile is needed to determine the ability of the drainage to accommodate rainwater discharge. The purpose of this study is to find out whether the drainage capacity is able or not to accommodate rainwater discharge. Then proceed with redesigning the drainage dimensions if the study results show insufficient drainage dimensions to accommodate flood discharge. The research method uses descriptive qualitative. Data collection begins with conducting field surveys to measure the dimensions of the existing drainage channel, including measuring the channel's width, height, and slope. The data needed in this study are rainfall data for at least ten years used to calculate the planned flood discharge and land cover maps to calculate the flow coefficient. The research showed that 24 out of 29 channel segments needed to be enlarged in dimension. Of the 24 channel segments, 70 percent of the channels require cleaning of sediment and channel maintenance so that rainwater can flow and inundation does not occur again.